The Influence Of Leadership And Communication On Organizational Performance Through Job Satisfaction At SD Luqman Al Hakim Surabaya - Wardono, Gunarto; Sutomo; Handayani, Sari; Zainuddin, Ahmad; Sumunu, Trenggono (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of leadership and communication on employee performance with job satisfaction as a mediating variable at SD Luqman Al Hakim Surabaya. In particular, this study examines: (1) the influence of leadership on employee performance, (2) the influence of communication on employee performance, (3) the influence of leadership on employee performance through job satisfaction, and (4) the influence of communication on employee performance through job satisfaction. The research population is all employees of SD Luqman Al Hakim Surabaya, with a sample of 100 respondents determined through simple random sampling techniques. Data analysis was carried out using the Partial Least Square (PLS) approach with the help of SmartPLS 4.0 software. The results of the study show that leadership has a positive and significant effect on employee performance, as well as communication has a positive and significant influence on employee performance. In addition, job satisfaction has been shown to significantly mediate the relationship between leadership and employee performance, as well as communication with employee performance. Thus, job satisfaction has an important role in strengthening the influence of leadership and communication on improving employee performance at SD Luqman Al Hakim Surabaya.